Seeking fair treatment from the AIDS epidemic to national health care reform - Daniels, Norman (Oxford Univ. Press, 1995)
Seeking Fair Treatment makes a major contribution to the health care debate and forces us to examine the current state and pace of health care reform in this country. Whether or not the present health care system emerges fundamentally changed (in whole or in part), the lessons of the AIDS epidemic are lessons we must all take to heart if we are to succeed in treating each other fairly through health care reform. Arguing passionately that access to health care is not merely a goal for a just society, but a requirement, Norman Daniels provides a framework for coming to terms with one of the great moral crises of our time
Keywords: AIDS; Droit de mourir; Ethische aspecten; Gezondheidszorg; Syndrome d'immunodéficience acquise - prévention et contrôle; Ethik; Gesundheitswesen; AIDS (Disease) -- Patients -- Medical care -- Moral and ethical aspects -- United States; Acquired Immunodeficiency Syndrome -- prevention & control; Health Care Reform; Health care reform -- United States; Right to Die; Right to health care -- United States; Aids; Medizinische Versorgung; Gesundheitsökonomie; Gesundheitspolitik; Sozialethik; USA